2014
DOI: 10.18632/oncotarget.1628
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin sensitizes anticancer effect of dasatinib in head and neck squamous cell carcinoma cells through AMPK-dependent ER stress

Abstract: Head and neck squamous cell carcinoma (HNSCC) is an important endemic disease in Taiwan with aggressive course and dismal outcome. Dasatinib is a Bcr-bl and Src kinase inhibitor that has potential against HNSCC. We recently disclosed that EGFR degradation is critical for dasatinib-induced apoptosis. Here, we further demonstrate that AMPK-dependent ER stress is responsible for this event. Dasatinib induced ER stress which mediated EGFR degradation in a c-cbl-dependent manner. AMPK activation induced by dasatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…We identified 11 articles with experimental studies that were in vitro and in vivo animal studies that analyzed the effect of metformin in HNSCC [20,28,45,46,[49][50][51][52][53][54][55] 2 of these studies presented the most important and complete results. Vitale-Cross et al [46] showed that metformin reduced the growth of HNSCC cells and diminished their mTORC1 activity by both AMPK-dependent and AMPK-independent mechanisms.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…We identified 11 articles with experimental studies that were in vitro and in vivo animal studies that analyzed the effect of metformin in HNSCC [20,28,45,46,[49][50][51][52][53][54][55] 2 of these studies presented the most important and complete results. Vitale-Cross et al [46] showed that metformin reduced the growth of HNSCC cells and diminished their mTORC1 activity by both AMPK-dependent and AMPK-independent mechanisms.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Previous reports have demonstrated that metformin enhances the effect of chemotherapy and radiotherapy by promoting the AMPK-autophagy signaling pathway (15)(16)(17)(18)(19). Therefore, it is expected that metformin would potentiate the cytotoxicity of 5-ALA-PDT.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have identified that metformin enhances the cytotoxicity of chemotherapy by promoting the AMPK-autophagy pathway (15)(16)(17)(18). In addition, metformin has been demonstrated to cause cell death in radiosensitized cancer cells and radioresistant cancer stem cells by activating AMPK and suppressing mTOR (19).…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrated that ER stress is elevated by the combination of metformin and FTY720. In previous studies, metformin has been found to induce ER stress in various carcinoma cells, such as liver, prostate, and head and neck squamous cell carcinoma [44][45][46]. Meanwhile, several studies determined that metformin attenuates ER-stress in pancreatic beta and cardiac epithelial cells [47,48].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%